Linear Morphometric Analysis of Auricular Measurements of a Nigerian Igbo population - Oladipo, Gabriel Sunday; Adheke, Oghenefego Michael; Eke, Janet Nneoma (Anthropological Review, 2023)
The human ear (auricle) is an important body component in biometric studies and forensic identification. The purpose of this study was to evaluate linear auricular morphometric measurements of a Nigerian Igbo population. 300 participants (142 males to 158 females) of at least 16 years of age were randomly recruited from settlements in the South-Eastern states of Nigeria. The participants were made to sit in a Frankfort horizontal position and auricular measurements such as total ear height (TEH), ear width (EW), lobule height (LH) and lobule width (LW) were obtained using a digital vernier caliper (validated by calibrating to 0.01mm). The ear index (EI) and lobule index (LI) were calculated using the measurements. Data obtained were analyzed using the Statistical Package for the Social Sciences (SPSS version 23.0). The following mean values were recorded for males: TEH [Right (R) = 47.01±6.30, Left (L) = 46.24±5.85], EW (R = 25.06±4.14, L = 24.68±4.32), LH (R = 13.92±2.61, L = 13.99±2.18), LW (R = 12.99±2.30, L = 13.30±1.94), EI (R = 53.47±7.23, L = 53.28±6.69) and LI (R = 95.17±18.12, L = 96.80±18.56); for females, TEH (R = 48.25±6.83, L = 48.25±6.24), EW (R = 25.19±3.93, L = 24.57±4.21), LH (R = 14.44±2.67, L = 14.89±2.55), LW (R = 13.37±2.26, L = 13.78±2.04), EI (R = 52.50±6.85, L = 50.93±7.05) and LI (R = 94.60±19.59, L = 94.30±16.63). Gender differences were highly significant regarding total ear height, lobular length and width, as well as the ear index of the left auricle. This study provides a baseline data for auricular morphometrics of adult Nigerian Igbos and could be used as an ergonomic guide towards the creation of hearing aids in the future and to solve possible forensic issues associated with identification of remains.